Produksi Bioetanol Berbahan Ampas Tebu Dan Sabut Kelapa Dengan Proses Fermentasi - Distilasi - Ardiani, Salsha; Yerizam, Muhammad; Yuliati, Selastia (Peneliti.net, 2024)
The high demand for fuel in Indonesia is currently the main crisis for the lack of fuel oil (BBM). So that alternative energy plays an important role in overcoming bad situations like today, by utilizing waste from abundant natural resources through this research it can create bioethanol as an alternative energy made from bagasse and coconut coir. In the process of making bioethanol using fermentation and distillation methods through various processes such as lignification and hydrolysis to increase the glucose content so that the two materials can be fermented and produce good bioethanol. Sugarcane bagasse and coconut coir are fermented using yeast with urea substituted as yeast nutrition in the bioethanol fermentation process, where urea is used with variations of 1gr, 1.5gr, 2gr, 2.5gr, and 3gr. After the urea variation samples were analyzed from this study for the bioethanol content, the sample which had the highest bioethanol content based on the urea variation produced a bioethanol content of 25.1% with 2gr yeast and 3g urea, the optimal fermentation time was 5 days, with a refractive index obtained 1, 3522